Pharmacogenetic markers of CYP2B6 associated with efavirenz plasma concentrations in HIV-1 infected Thai adults - Chonlaphat Sukasem (2018)
Aims: To investigate the frequency of CYP2B6 polymorphisms and the influence of haplotype structure on plasma efavirenz concentrations in Thai adults with HIV-1 infection. Methods: Genotyping of nine single nucleotide polymorphisms (SNPs, c.64C>T, c.499C>G, c.516G>T, c.785A>G, c.1375A>G, c.1459C>T, g.3003T>C, g.18492C>T and g.21563C>T) of CYP2B6 were performed using real-time PCR-based allelic discrimination on blood samples from 52 HIV-infected adults who had received an efavirenz-based regimen. Plasma efavirenz concentrations were measured by high performance liquid chromatography. Results: The minor allele frequencies for c.64C>T, c.516G>T, c.785A>G, g.3003C>T, g.18492T>C and g.21563C>T were 0.087, 0.365, 0.413, 0.308 and 0.356, respectively. However, no variant alleles were identified for three SNPs (c.499 C>G, c.1375 A>G and c.1459 C>T). Efavirenz plasma concentrations were significantly associated with c.516G>T (P= 0.0095), c.785A>G (P= 0.0017), g.21563C>T (P= 0.0036) and g.18492C>T (P= 0.0011). The composite CYP2B6 of three SNPs (c.516G ≥ T, c.785A ≥ G and g.21563C ≥ T) genotypes were significantly associated with higher efavirenz concentrations. Conclusions: Our data indicate that the GAC-CYP2B6 haplotype is associated with higher plasma efavirenz concentrations in HIV-infected Thai adults. © 2012 The Authors. British Journal of Clinical Pharmacology © 2012 The British Pharmacological Society.